Experimental Investigation on Stiffness and Strength of Single-Lap Z-Pinned Joints in a Laminated CFRP Stress-Ribbon Strip - Aleksandr K. Arnautov; Vladimir Kulakov; Janis Andersons; Viktor Gribniak; Algirdas Juozapaitis (The Baltic Journal of Road and Bridge Engineering, 2016)
Carbon fiber-reinforced polymer (carbon-polymer) is an advanced lightweight composite material with high strength and excellent resistance to corrosion and fatigue. Over the past decades, application of fiber-reinforced polymers has been spread from the aerospace to other branches of industry such as automobile and civil engineering. Unidirectional carbon-polymers have a high potential for replacing steel in tensile members. Recently, the first carbon-polymer stress-ribbon bridge has been constructed in Germany. The non-laminated strip-loop carbon-polymer thin strips were used as the load bearing components in this bridge. In comparison with the laminated components, the applied cables are characterized by a more uniform strain distribution though reduced structural integrity. Alternative jointing technologies of carbon-polymer laminates are considered in this paper with an intention to increase the structural integrity and reliability of the production. Tensile behavior of the single-lap joints was investigated experimentally. Three types of the joints were considered. Adhesive joint was set as the reference. The overlap region of the mechanically fastened joints was produced using 9, 25, or 36 steel needles (z-pins) of 1 mm diameter. The proposed hybrid joints were additionally connected with adhesive increasing the load-bearing capacity of the reference joint up to 230%. Concerning the brittle fracture of the adhesive counterparts, the extended progressive failure process within the hybrid joints is responsible for the improvement.